Non-Native Arabic Learner’s Self-Regulated Learning And Social Media Usage Influence Learning Of Arabic Language - Xuan Di; Wail Muin Ismail; Muhammad Azhar Zailani (Ijaz Arabi Journal of Arabic Learning, 2022)
In recent years, researchers verified that Social media exist as a “natural alliance” with self-regulated learning in the educational affair. Social media has become the most popular way to communicate and learn foreign languages. Language learners can easily accept the integration of social media in language practice. This study intends to investigate Arabic learners’ Self-regulated learning strategies (SRLS) and social media usage (SMU). Such as using Facebook, MySN, Twitter, YouTube, Pinterest, and the like in Arabic learning in Malaysian universities and how social media can support or promote learners’ self-regulated learning to improve academic achievement. The finding indicated that Arabic learners’ SMU and SRLS with a positive correlation. The dimensions of SRLS, such as Metacognitive skills, Environmental structuring, and Persistence, are positively correlated to SMU, regardless of formal or informal learning style.